Mark ; v.1 Jesus, servant and savior - Hughes, R. Kent (Wheaton, IL Crossway, 1989)
Contents : v.1 : Mark 1-9:1. Includes bibliographical references and indexes.
Keywords: Bible. N.T. Mark I-IX -- commentaries